Adherence of bacteria to intraocular lenses: a prospective study. Issue 4 (April 1995) - Doyle, A; Beigi, B; Early, A; Blake, A; Eustace, P; Hone, R
Abstract : AIMS--The study was designed to investigate the bacterial flora of the operating field during routine cataract surgery and the source of intraocular lens contamination during the surgery. METHODS--The normal flora of the external eye and fornices of 17 patients undergoing selective cataract surgery was determined preoperatively. Swabs taken from the eyelid surface and lashes showed coagulase negative staphylococci (CNS) in 90%, Propionibacterium acnes in 62%, Corynebacterium sp in 18%, and Peptostreptococcus in 3% of the patients. The lower fornices of 70% had CNS, 47% P acnes, 6% Staphylococcus aureus, 6% Corynebacterium sp, and 6% Candida. RESULTS--A sterile PMMA intraocular lens was touched on the upper bulbar conjunctiva immediately before the surgery. Eighty two per cent of lenses grew CNS, 18% P acnes, 18% Bacillus sp, 12% S aureus, and 6% Corynebacterium sp. A second sterile PMMA intraocular lens was left on the drape and near the eye during surgery. Forty seven per cent of these cultured CNS, 12% Corynebacterium sp, and 6% Bacillus sp. A high count of bacteria in the operating field, especially CNS and P acnes can contribute to postoperative inflammation and endophthalmitis. CONCLUSION--Special measures are needed before and during the surgery to reduce the chance of intraocular inoculation of these bacteria. Use of proper culture media and techniques are necessary to identify these organisms, especially anaerobes, in postoperative inflammation.